2013
DOI: 10.1371/journal.pone.0080203
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Detection of prionemia in TSE-Infected Cervids and Hamsters

Abstract: Blood-borne transmission of infectious prions during the symptomatic and asymptomatic stages of disease occurs for both human and animal transmissible spongiform encephalopathies (TSEs). The geographical distribution of the cervid TSE, chronic wasting disease (CWD), continues to spread across North America and the prospective number of individuals harboring an asymptomatic infection of human variant Creutzfeldt-Jakob Disease (vCJD) in the United Kingdom has been projected to be ~1 in 3000 residents. Thus, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 59 publications
3
86
0
Order By: Relevance
“…The RT-QuIC assay was shown to be applicable for the detection of PrP TSE in the whole blood of CWD-infected cervids and TME-infected hamsters, during both the preclinical and clinical phases of the disease, with approximately 94 % sensitivity and 100 % specificity (Elder et al, 2013). Moreover, it has been shown that limited cycles of freeze-thawing of the blood samples enhances the sensitivity of blood-borne prion detection by RT-QuIC during the preclinical phase of the disease (Elder et al, 2013).…”
Section: Real-time Quaking-induced Conversion (Rt-quic)mentioning
confidence: 99%
See 2 more Smart Citations
“…The RT-QuIC assay was shown to be applicable for the detection of PrP TSE in the whole blood of CWD-infected cervids and TME-infected hamsters, during both the preclinical and clinical phases of the disease, with approximately 94 % sensitivity and 100 % specificity (Elder et al, 2013). Moreover, it has been shown that limited cycles of freeze-thawing of the blood samples enhances the sensitivity of blood-borne prion detection by RT-QuIC during the preclinical phase of the disease (Elder et al, 2013).…”
Section: Real-time Quaking-induced Conversion (Rt-quic)mentioning
confidence: 99%
“…The RT-QuIC assay was shown to be applicable for the detection of PrP TSE in the whole blood of CWD-infected cervids and TME-infected hamsters, during both the preclinical and clinical phases of the disease, with approximately 94 % sensitivity and 100 % specificity (Elder et al, 2013). Moreover, it has been shown that limited cycles of freeze-thawing of the blood samples enhances the sensitivity of blood-borne prion detection by RT-QuIC during the preclinical phase of the disease (Elder et al, 2013). This increased sensitivity may be due to the damaging effect of the thermal shock on the membranes of infected blood cells, which releases the intracellular components, including prions, thus increasing the in vitro nucleation and consequently the detection of PrP Cconverting activity (Elder et al, 2013).…”
Section: Real-time Quaking-induced Conversion (Rt-quic)mentioning
confidence: 99%
See 1 more Smart Citation
“…In some infected populations, CWD is a leading cause of cervid mortality and may negatively impact population dynamics (Dulberger et al, 2010;Sargeant et al, 2011). Both clinically and preclinically infected cervids harbour sufficient infectious prions to efficiently transmit disease (Hill & Collinge, 2003;Bishop et al, 2013;Elder et al, 2013). CWD can be transmitted by direct contact with infected animals, carcasses, bodily fluids, secretions or excreta (Mathiason et al, 2006;Saunders et al, 2012;Lacroux et al, 2014), or indirectly through uptake of infectious material shed into the environment (Miller & Williams, 2004;Mathiason et al, 2006;Saunders et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PrP TSE has been successfully detected in the following: in whole blood of experimentally infected mice and hamsters, in sheep with natural scrapie and experimental BSE, and in white-tailed deer afflicted with CWD (21)(22)(23); in buffy coats of hamsters and sheep experimentally infected with scrapie (24 -26), as well as in plasma of mice and hamsters with scrapie; and in sheep and white-tailed deer naturally and experimentally infected with scrapie and CWD, respectively (27)(28)(29)(30). However, it is still not fully understood in what blood component TSE infectivity and/or PrP TSE reside and whether and how blood contributes to the spread of the disease from the periphery to the brain.…”
mentioning
confidence: 99%